BIOCHEMICAL CHANGES IN BLOOD SERUM OF PIGS PATIENT TRICHUROSIS - Мельничук, В. В.; Назаренко, О. С.; Назаренко, С. І. (Scientific Progress & Innovations, 2015)
The results of hematological studies to determine the impact of the pathogen of trichurosis of pigs on blood serum biochemical parameters infested animals are presented. We established that trichurises’ parasites in the body of pigs leads to a significant reduction of total protein, albumin and increase of total bilirubin, indirect bilirubin and enzyme activity in blood serum. These data suggest about involvement of liver parenchyma in the pathological process, cardiac muscle and smooth muscles of the intestine.